Measuring Pharmaceutical Supply Performance at the Facility Level: A Standards-Aligned Study - Haviana, Evan; Hardi, Yuni; Jamal, Siti Aisyah; Aini, Nurul; Harifuddin, Harifuddin; Andalas, Ronny; Sugoro, Ramadhani Yusli Arbain (YCMM, 2024)
Reliable management of medicines and medical supplies is a prerequisite for high-quality pharmacy services. This study evaluates the performance of a Pharmacy Installation against national standards and identifies priority areas for improvement. We employed a descriptive–evaluative design using an assessment instrument aligned with the Directorate General of Pharmaceuticals and Medical Devices, Ministry of Health of the Republic of Indonesia (2017), covering two components: Resources (maximum 60) and Management (maximum 40). The results show a total score of 92.46/100, comprising Resources 56.06/60 and Management 36.40/40, classifying performance as compliant with the standard. Strengths are concentrated in operational processes (receipt, distribution, recording and reporting), while opportunities for improvement relate to data-driven planning, strengthening organisational/structural arrangements, and tightening inventory-control practices. Practical implications include implementing clear control parameters (e.g., reorder point and safety stock) and item-priority classifications (e.g., ABC–VED) to stabilise availability, reduce expiry risk, and improve cost efficiency. The study provides a comprehensive snapshot of compliance and a direction of continuous improvement for pharmacy installations.